A function of fascin1 in the colony formation of mouse embryonic stem cells. (1st June 2020) - Fan, Yan‐Lei; Li, Bo; Zhao, Hong‐Ping; Zhao, Hu‐Cheng; Feng, Xi‐Qiao
Abstract: Fascin1 is known to participate in the migration of cancer cells by binding to actin filaments. Recent studies evidenced that fascin1 also modulates processes such as the tumorigenesis and maintenance of pluripotency genes in cancer stem cells. However, the function of fascin1 in embryonic stem cells remains unclear. In this article, we report that fascin1 is highly expressed and widely distributed in mouse embryonic stem cells (mESCs), which are regulated by JAK‐STAT3 and β‐catenin. We found that the overexpression of fascin1 impairs the formation of mESC colonies via the downregulation of intercellular adhesion molecules, and that mimicking the dephosphorylated mutation of fascin1 or inhibiting phosphorylation with Gö6983 significantly enhances colony formation. Hyperphosphorylated fascin1 can promote the maintenance of pluripotency in mESCs via nuclear localization and suppressing DNA methyltransferase expression. Our findings demonstrate a novel function of fascin1, as a vital regulator, in the colony formation and pluripotency of mESCs and provide insights into the molecular mechanisms underlying embryonic stem cell self‐organization and development in vitro. Abstract : We discovered a novel function of fascin1 in the mouse embryonic stem cell (mESC) colony formation and pluripotency maintenance. We showed that an appropriate expression of fascin1 can improve the stemness and facilitate self‐renewal of mESCs, whereas overexpression of fascin1 disrupted the colony formation. The phosphorylation state changes of fascin1 manipulated mESCs' fates via influencing the expression of Dnmts and their cofactors. Hyperphosphorylated fascin1 can promote the pluripotency maintenance of mESCs via nuclear localization and suppress the genes expression of DNA methyltransferases.